Juggling access vs retention and academic performance: The experience of a lecturer teaching in an open, distance e-learning institution - le Roux, S. G. (South African Journal of Higher Education, 2024)
In response to the growing number of people requiring access to higher education, the student numbers at distance education institutions grew significantly over the last decade (Unisa 2013; 2020). Unfortunately, many students who enrol at open distance learning institutions are not ready for the demands of distance e-learning. More than half of students enrolled at the open distance learning institution where this study was done drop out and the reasons have been well researched (Joubert and Snyman 2018; Mashile, Fynn, and Matoane 2020). It seems that universities’ responses to Sustainable Development Goal 4 (SDG 4.3 ‒ equal access to technical, vocational and higher education) (Unesco 2021) may unintentionally have created new vulnerabilities for the very group of people they have targeted for progress to end poverty, hunger and discrimination. As nearly a third of all students in South Africa are enrolled at Africa’s largest open distance learning institution (Unisa 2018), it becomes crucial not only to increase access, but simultaneously to prioritise student retention and academic performance. This raises the question: How can and should lecturers teaching at distance-education institutions optimise the online teaching and learning environment in order to bridge the gap between access targets and academic performance targets? Following an autoethnographic research design, I share my own experiences of teaching two year-modules of the Bachelor of Education (B.Ed) Foundation Phase programme offered via a continuous assessment (CA) approach. Two theoretical frameworks, namely the socio-critical model of Subotzky and Prinsloo (2011, 184), and Luna’s (2018) theory of layers of vulnerability guided my understanding of the challenges associated with distance learning as well as my research design. My study reveals that the promise of CA does not always convert to optimal performance, and that contextual factors in distance education have a powerful impact on academic achievement despite the effort made by lecturers.